Trade policy and transport costs in Uganda - Nichodemus Rudaheranwa (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
Recent studies on trade policy for low-income countries have established that high transport costs associated with poor quality infrastructure in countries such as Uganda represent a barrier to trade and an additional source of protection to domestic producers of import competing goods. This study updates and extends the analysis of Milner et al (2000) for Uganda in the 1994 to compare with the situation in the early 2000s. The results show that trade policy barriers have been further reduced and, in general, transport costs have fallen, although not dramatically. Transport costs remain a significant trade barrier, equivalent to effective protection of over 20% and an implicit tax on exports of over 25% (and up to 50% on air freight). Simulation of the protection effects under the new EAC Customs Union shows that overall the level of tariff protection will increase but any adverse impacts could be offset by greater efficiency at Customs and ports and additional investment to reduce infrastructurerelated transport costs.
Keywords: F14; O10; O55; 330; Effective Protection; Transport Costs; Trade; Uganda